Denosumab in Cementless Total Hip Arthroplasty: Multivariate Reanalysis of 3D Femoral Stem Migration and the Influence on Outliers - Finnilä Sami; Löyttyniemi Eliisa; Aro Hannu T (WILEY, 2022)
In cementless total hip arthroplasty, adequate implant stability is necessary for the success of osseointegration and rapid clinical recovery. Postoperative femoral stem migration, measured by radiostereometric analysis (RSA), defines the initial stability achieved during surgical implantation. In a recent trial of 65 postmenopausal women randomized 1:1 denosumab:placebo, denosumab failed to reduce the initial migration of a cementless femoral stem despite the successful prevention of periprosthetic bone loss. The trial applied the current RSA standard, which examined stem migration on an axis-by-axis basis and did not consider more complex three-dimensional (3D) migration. Therefore, we performed a reanalysis of the trial data using a multivariate hierarchical linear mixed model (LMM). As an additional limitation, the data included influential outliers. Women with normal bone mineral density exhibited significantly (p = 0.036) less stem subsidence compared with osteopenic and osteoporotic women. Denosumab significantly decreased the variance of stem migration in osteopenic and osteoporotic women. The mean magnitude of 3D stem migration did not differ between denosumab-treated and placebo-treated women (p = 0.820). After application of a common statistical definition for RSA outlier identification, there were eight (12%) outliers, six in the placebo group and two in the denosumab group (p = 0.149). After exclusion of the outliers, the repeated LMM analysis demonstrated a trending difference in 3D stem migration (p = 0.086), with a significant difference of z-axis rotation (valgus-varus tilt) of the femoral stem (p = 0.029). The observed effect size was small and without clinically important differences in postoperative recovery. Based on a Monte Carlo simulation with random-generated 3D migration data, multivariate LMM showed greater statistical power than univariate analyses. The application of hierarchical LMM facilitated the analysis of implant migration as a factual 3D event. The observed trend in the lower number of RSA outliers in denosumab-treated subjects warrants powered large-scale trials.